Correlation of Heart Rate Variability and 24- hour Mean Heart Rate with TIMI Risk Score in Acute ST-Segment Elevation Myocardial Infarction - Chakravortty, SK; Khan, MR; Kundu, S; Barua, SK; Dutta, B; Uddin, MN; Islam, AKMM; Ullah, M; Majumder, AAS (Cardiovascular Journal, 2012)
Background: Thrombolysis In Myocardial Infarction (TIMI) risk score, heart rate variability (HRV) and 24hour mean heart rate all are important predictor of prognosis after ST segment elevation myocardial infarction(STEMI). Correlation among these factors has not been studied thoroughly. Methods: This study was conducted in NICVD (National Institute of Cardiovascular Diseases), Dhaka, from July 2008 to June 2009. Total 105 STEMI patients were included in the study. TIMI risk score were calculated and each patient under went 24hour Holter monitoring. SDNN for HRV and mean RR interval for mean heart rate were recorded. Results : Ninety one patients (mean age 53.9 ± 10.8 years), 86.7% were males and 14( mean age 59.8 ± 8.8 years), 13.3% were female. Stratification of subjects by TIMI risk score shows that nearly 60% had risk score in the range of 3 – 7, 17. % between 0 – 2 and 24% 8 or more than 8.SDNN and RR interval stratified by TIMI risk score demonstrates that both the variables decreases significantly with the increase of TIMI risk score. Among the TIMI risk groups SDNN values were 120.0 ± 19, 871.0 ± 20.5 and 40.9 ± 6.4 msec in mild, moderate and high risk group respectively(p=<0.001). Mean RR were 836.8 ± 121.0, 776.7 ± 130.3 and 649.7 ± 75.5 msec in low, intermediate and high risk group respectively(p<0.001). There was a significant correlation between depressed SDNN and high TIMI risk score (r=.893, p=.001). High TIMI risk score also showed a negative correlation with mean RR interval (r=-574, p<0.001). Mean RR and SDNN show a perfect linear relationship (r = 0.657, p < 0.001). Conclusion: It was observed that depressed heart rate variability and increased 24-hours mean heart rate correlates with high TIMI risk score after acute ST-elevation myocardial infarction. Keywords: TIMI risk score; Heart rate variability; STEMI DOI: http://dx.doi.org/10.3329/cardio.v4i1.9383 Cardiovasc. J. 2011; 4(1): 8-12